(E)3-2-(1-(2,4-Dihydroxyphenyl)ethyldeneamino)phenyl)-2-methylquinazoline-4(3H)-one Schiff Base and Its Metal Complexes: A New Drug of Choice against Methicillin-Resistant Staphylococcus aureus - K. Siddappa; Sunilkumar B. Mane; Deene Manikprabhu (Bioinorganic Chemistry and Applications)
The 3-(2-aminophenyl) quinazolin-2-methyl-4(3H)-one and 2,4-dihydroxyacetophenone undergo condensation to afford (E)3-2-(1-(2,4-dihydroxyphenyl)ethyldeneamino)phenyl)-2-methylquinazoline-4(3H)-one Schiff base (DHPEAPMQ). The newly synthesized Schiff base (DHPEAPMQ) and its metal complexes were evaluated for their antimicrobial activity against methicillin-resistant Staphylococcus aureus isolated from the Gulbarga region in India. The Cu(II), Ni(II), and Zn(II) complexes of Schiff base (DHPEAPMQ) showed good antimicrobial activity. So, this could be a new drug of choice.